The Role Of Social Psychology In Individual Cognitive And Social Development - Erwin Eka Saputra; Chairan Zibar L. Parisu (FKIP UNSULTRA, 2025)
Social psychology plays a crucial role in understanding how individuals develop cognitively and socially through interactions with their surroundings. This study aims to analyze the relationship between social psychology and individual cognitive and social development based on recent literature. The research method used is a literature review by examining various relevant scientific sources. The findings indicate that social interactions with family, peers, and the educational environment significantly contribute to cognitive development, including the enhancement of critical thinking skills, problem-solving abilities, and information processing. Furthermore, social aspects such as emotional support, effective communication, and collaborative experiences play a role in shaping strong social skills, including empathy, social adaptation, and cooperation. Vygotsky's theory of the Zone of Proximal Development (ZPD) and Bandura's concept of social learning emphasize that interaction with more experienced individuals can accelerate one's cognitive development. However, an unsupportive environment, such as limited social interactions or negative social pressure, may hinder this growth. Therefore, educational strategies that prioritize healthy social interactions and supportive learning environments are essential for optimizing individual development. This study provides valuable insights for educators, parents, and policymakers in fostering an environment that supports balanced cognitive and social growth.